2007
DOI: 10.3233/jad-2007-12204
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum C-Reactive Protein Concentration in Bosnian Patients with Probable Alzheimer's Disease

Abstract: Studies indicate that inflammatory mechanisms may play an important role in the pathogenesis of Alzheimer's disease (AD). C-reactive protein (CRP), marker and mediator of inflammation, has been detected in lesions typical for the affected areas of AD brain. There have been conflicting reports on serum CRP concentration in AD. Scarce data exist on association of CRP and measures of adiposity in AD patients. Thus, we investigated serum CRP concentration in fifteen overweight institutionalized patients with proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…This approach is not disease specific and can be easily applied to any sub-acute inflammatory disease. Similar to the observations in our current study on patients with ALS, CRP concentrations were found to be higher in patients with AlzheimerÕs disease compared with controls (21)(22)(23), and also in persons before clinical onset of dementia (24), although a very recent study showed on the contrary a more rapid cognitive decline in patients with AlzheimerÕs disease with lower CRP levels (25). a wrCRP value of less than 5 mg ⁄ l), but a sub-clinical systemic low-grade inflammatory process was revealed when these results were compared with our database of healthy individuals.…”
Section: Low-grade Systemic Inflammation In Alssupporting
confidence: 91%
“…This approach is not disease specific and can be easily applied to any sub-acute inflammatory disease. Similar to the observations in our current study on patients with ALS, CRP concentrations were found to be higher in patients with AlzheimerÕs disease compared with controls (21)(22)(23), and also in persons before clinical onset of dementia (24), although a very recent study showed on the contrary a more rapid cognitive decline in patients with AlzheimerÕs disease with lower CRP levels (25). a wrCRP value of less than 5 mg ⁄ l), but a sub-clinical systemic low-grade inflammatory process was revealed when these results were compared with our database of healthy individuals.…”
Section: Low-grade Systemic Inflammation In Alssupporting
confidence: 91%
“…These findings are in harmony with those of Zaciragic et al 50 and Ho et al 51 In brain tissue, the pathophysiology of CRP accumulation is complex because of the requirement of systemically produced CRP to cross the BBB. However, it has been established that during inflammatory conditions, the BBB becomes dysfunctional, enabling proteins normally only found in serum to enter the cerebrospinal fluid, so the transit of circulating CRP across the BBB is the most likely potential source of cerebral CRP.…”
supporting
confidence: 87%
“…These results suggest a direct functional effect elicited by CRP and may be explanatory for, at least in part, the pathogenesis of Alzheimer's disease . However, data to support this are scarce, and a direct inference based on comparative CRP levels should not be made with respect to the pathogenesis of Alzheimer's disease …”
Section: Crp and Ageing‐related Diseasementioning
confidence: 93%